2021
DOI: 10.36941/mjss-2021-0038
|View full text |Cite
|
Sign up to set email alerts
|

Social Challenges to the Education of Orphaned and Vulnerable Children in Eleme, Nigeria

Abstract: Nigerian children under prolonged suffering because of loss of parents are faced with several challenges such as dropping out of school; in some cases, they may even be taken out of school to care for the home.  In this study, we determined the challenges (financial, emotional and psychological) to the education of orphaned and vulnerable children in Eleme Local Government Area of Rivers State, Nigeria. All the 396 orphans in orphanages in the study Area constituted the study population. A Questionnaire captio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…The community’s negative perceptions were also evident in parents’ refusal to enroll children in orphanage-owned schools, leading to a feeling of stigmatization by the children. This study not only supports findings from previous works reporting feelings of stigmatization among the children ( 37 , 38 ), but it also shows how this contributes to the stigmatization of the children. Previous studies ( 39 , 40 ) have identified orphanage children and adolescents with emotional issues such as post-traumatic disorders.…”
Section: Resultssupporting
confidence: 91%
“…The community’s negative perceptions were also evident in parents’ refusal to enroll children in orphanage-owned schools, leading to a feeling of stigmatization by the children. This study not only supports findings from previous works reporting feelings of stigmatization among the children ( 37 , 38 ), but it also shows how this contributes to the stigmatization of the children. Previous studies ( 39 , 40 ) have identified orphanage children and adolescents with emotional issues such as post-traumatic disorders.…”
Section: Resultssupporting
confidence: 91%
“…Although families are ideally the primary source of protection against these risks, challenges within families can prevent them from providing the necessary care and protection required by OVC (Martin et al, 2018). Previous research by Eneji and Archibong (2021) suggests that the lack of affection, proper housing, education and emotional support serves as precursors to vulnerability.…”
Section: Literature Review On the Challenges Faced By Ovcs In Zimbabwementioning
confidence: 99%
“…These challenges often drive OVC towards more entrenched issues such as alcohol and drug abuse as coping mechanisms for their anxiety, as evidenced by Mashayahanya's (2017) study. During interactions with the respondents, it also became apparent that the extended family sometimes neglects the psychological well-being of orphans, a sentiment echoed by Eneji and Archibong (2021). In the Zimbabwean context, where discussions about death with children are rare, grieving children face significant obstacles in the healing process.…”
Section: Psycho-social Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a woman if found at all is believed to be cursed. The scenario has some reverberating consequences in form of high level immorality and prostitution, abortions, increasing rate of cohabitations and the birth of bastards (Eneji & Archibong, 2021). Feminism also known as feminists' sensitivity, gender equality and many more are foreign values that have now reached the shores of Africa (Bhutler, 1999;Effah-Atoe, 2006).…”
Section: Introductionmentioning
confidence: 99%